2018
DOI: 10.3892/mmr.2018.9719
|View full text |Cite
|
Sign up to set email alerts
|

α‑lipoic acid protects against carbon tetrachloride‑induced liver cirrhosis through the suppression of the TGF‑β/Smad3 pathway and autophagy

Abstract: α-lipoic acid (ALA) is a naturally occurring antioxidant with protective effects against various hepatic injuries. The aim of the present study was to investigate the mechanisms by which ALA protects the liver from carbon tetrachloride (CCl4)-induced liver cirrhosis. The widely used liver cirrhosis rat model was established via an intraperitoneal injection of 2 mg/kg 50% CCl4, three times/week for 8 weeks. Simultaneously, 50 or 100 mg/kg ALA was orally administrated to the rats every day for 8 weeks. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Furthermore, the treatment with ALA of rats with hepatic fibrosis resulted in a reduction in the activity of aspartate transaminase (AST) and alanine transaminase (ALT), improveed hepatic injury by decreasing the deposition of collagen fibers, and restoreed the Akt/mammalian target of rapamycin (mTOR) pathway. All this is possible thanks to its ability to inhibit the TGF-β/Smad3 pathway with consequent suppression of autophagy [65]. In addition, clinical trials consisting in ALA supplementation in patients with NAFLD have reported a modulation of some of the oxidative stress related parameters, including serum malondialdehyde levels and total antioxidant status, as well as a modification of the adipokine profile, known to play a key role in the progression of NAFLD [66,67].…”
Section: Natural Sulfur-containing Compounds For the Treatment Of mentioning
confidence: 99%
“…Furthermore, the treatment with ALA of rats with hepatic fibrosis resulted in a reduction in the activity of aspartate transaminase (AST) and alanine transaminase (ALT), improveed hepatic injury by decreasing the deposition of collagen fibers, and restoreed the Akt/mammalian target of rapamycin (mTOR) pathway. All this is possible thanks to its ability to inhibit the TGF-β/Smad3 pathway with consequent suppression of autophagy [65]. In addition, clinical trials consisting in ALA supplementation in patients with NAFLD have reported a modulation of some of the oxidative stress related parameters, including serum malondialdehyde levels and total antioxidant status, as well as a modification of the adipokine profile, known to play a key role in the progression of NAFLD [66,67].…”
Section: Natural Sulfur-containing Compounds For the Treatment Of mentioning
confidence: 99%
“…In our study, we aimed to investigate the effects of ALA and NAC and their combination on DEN-initiated HFDpromoted hepatic lesions. ALA is an antioxidant with protective effects against various hepatic injuries [13,14]. ALA supplementation was reported to reduce lipid accumulation, inflammation, and oxidative stress in the liver of MCD-and HFD-fed mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, HFD composition [24] and the used doses of DEN [25], ALA [13,14] and NAC [19,20] were selected with respect to previous studies.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It has abrogated xenobioticinduced fibrosis, necrosis, and steatosis in rats. [16][17][18] In the light of the aforementioned information, the present study examined the protective effects of MT and ALA against LPV/r-induced hepatic alterations in rats.…”
Section: Introductionmentioning
confidence: 99%